How strange the change : language, temporality, and narrative form in peripheral modernisms - Caplan, Marc (Stanford studies in Jewish history and culture., 2011)
Marc Caplan argues that the literatures of ostensibly marginal modern cultures are key to understanding modernism. Caplan undertakes an unprecedented comparison of 19th-century Yiddish literature and 20th-century Anglophone and Francophone African literature and reveals unexpected similarities between them.